Two Foundation Stones of Radiation Medicine - VERMA, N.K. (SCHOOL SCIENCE, 2007)
MODERN PHYSICS may be said to date from 1895 when Roentgen discovered X-rays. Two other major discoveries followed in quick succession, namely, the discovery of radioactivity by Becquerel in 1896 and the discovery of radium by Madam Curie in 1898. These epoch making discoveries not only revolutionised physics but have proved to be of immense application in the medical field. Madam Curie’s birth centenary was recently celebrated in November 1967. This article gives an account of the discovery and applications of the two foundation stones of radiation medicine X-rays and radium.